Part A: The equation of the ship's path is ![y=3x-1](https://tex.z-dn.net/?f=y%3D3x-1)
Part B: The two ships sails perpendicular to each other.
Explanation:
Part A: It is given that
and point (2, 5)
Substituting these in the slope intercept form, we have,
![y-y_{1}=m\left(x-x_{1}\right)](https://tex.z-dn.net/?f=y-y_%7B1%7D%3Dm%5Cleft%28x-x_%7B1%7D%5Cright%29)
![\begin{aligned}y-5 &=3(x-2) \\y-5 &=3 x-6 \\y &=3 x-1\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7Dy-5%20%26%3D3%28x-2%29%20%5C%5Cy-5%20%26%3D3%20x-6%20%5C%5Cy%20%26%3D3%20x-1%5Cend%7Baligned%7D)
Thus, the equation of the ship's path in slope intercept form is ![y=3x-1](https://tex.z-dn.net/?f=y%3D3x-1)
Part B: The equation of the second ship is ![x+3 y-6=0](https://tex.z-dn.net/?f=x%2B3%20y-6%3D0)
Let us bring the equation in the form of slope intercept form.
![\begin{aligned}3 y &=-x+6 \\y &=-\frac{1}{3} x+2\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D3%20y%20%26%3D-x%2B6%20%5C%5Cy%20%26%3D-%5Cfrac%7B1%7D%7B3%7D%20x%2B2%5Cend%7Baligned%7D)
Thus, from the above equation the slope is ![m=-\frac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B3%7D)
To determine the two ships sailing perpendicular to each other, we have
![m_{1} \times m_{2}=-1](https://tex.z-dn.net/?f=m_%7B1%7D%20%5Ctimes%20m_%7B2%7D%3D-1)
where
and ![m_{2}=-\frac{1}{3}](https://tex.z-dn.net/?f=m_%7B2%7D%3D-%5Cfrac%7B1%7D%7B3%7D)
![\begin{aligned}3 \times-\frac{1}{3} &=-1 \\-1 &=-1\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D3%20%5Ctimes-%5Cfrac%7B1%7D%7B3%7D%20%26%3D-1%20%5C%5C-1%20%26%3D-1%5Cend%7Baligned%7D)
Since, both sides of the equation are equal, these two ships sails perpendicular to each other.